The hyperventilation syndrome - Ames, Frances (Department of Public Health and Family Medicine, 2020)
The hyperventilation syndrome is the name given to a distinctive group of symptoms and signs which are caused by an increase in the depth and rate of breathing. This abnormal breathing is nearly always the result of emotional stress. The association between emotional stress and disorders of breathing is well-known: sighing with grief, gasping with rage, panting with fear, heaving with resentment. Of its origin, Darwin said, "Men, during numberless generations, have endeavoured to escape from their enemies by headlong flight, or by violently struggling with them; and such great exertions will have caused the heart to beat rapidly, the breathing to be hurried, the chest to heave and the nostrils to be dilated...And, now, whenever the emotion of fear is strongly felt, though it may not lead to any exertion, the same results tend to reappear through the force of inheritance and association." Cannon (1920) described hyperventilation as a preparation for flight or fight: "The forced respirations in deeply emotional experiences can be interpreted, therefore, as an anticipatory reduction of the carbon- dioxide in the blood, a preparation for the augmented discharge of carbon- dioxide into the blood as soon as great muscular exertion begins." Primitive man could and did take to his heels or use his fists if afraid. Modern man, inhibited by cultural and social traditions of behaviour, is unable to do so. So the age-old physiological preparation for flight or fight is not carried over into any functional motor activity. This is when trouble arises. A strong emotional reaction with no motor outlet turns on itself to cause physical upset . In this paper a study is made of the symptoms and signs by which to recognize this syndrome, and of some of the physiological mechanisms which are brought into operation.